Foreign parts : German and Austrian actors on the British stage 1933-1960 - Dove, Richard (Germanic literatures, 2017)
Foreign Parts offers a case study in Anglo-German relations in the theatre. How British was the British theatre during and after the Second World War? This book tells the unique story of five German-speaking actors who, after arriving as refugees from Nazi Germany, made the transition to the British stage in a period of heightened nationalism before and during World War II. While the emotional intensity of their performances won the applause of audiences and the approval of critics, their success also depended on the support of British theatre personalities - from Alec Clunes and Tyrone Guthrie to actors Sybil Thorndike and John Gielgud. The book also recounts their role in British propaganda broadcasts to Germany, including Martin Miller's satirical impersonation of his fellow-Austrian Adolf Hitler and Lucie Mannheim's anti-Nazi version of the popular hit 'Lilli Marlene'.